KINERJA OMBUDSMAN REPUBLIK INDONESIA PERWAKILAN PROVINSI RIAU DALAM PENANGANAN LAPORAN MASYARAKAT KOTA PEKANBARU - Marbun, Fibrisio H; Tua R.F.S, Harapan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The act of maladministration is a behavior that is not in according with the principle of exellent public services that resulted in material or immaterial losses to society. Maladministration is also incompatible with the principles of good governance , clean and efficient . Representatives of Ombudsman of the Republic of Indonesia Riau Province is a representative of the Ombudsman of the Republic of Indonesia in Riau that serves to monitor and prevent acts of maladministration which occurred in the province of Riau . Representatives of Ombudsman of the Republic of Indonesia Riau Province oversee implementation of public service with follow up reports / complaints from the community to produce a decision in the form of recommendations and suggestions . The purpose of this study was to analyze the performance and also the factors that influence the performance of the Ombudsman of the Republic of Indonesia Representative Riau Province in Handling Reports Pekanbaru city community .The concept of theory that researchers use is performance. By looking at the responsiveness , responsibility and accountability of the Ombudsman Representative Riau Province . This study uses qualitative research methods with an assessment of descriptive data . In collecting the data , researchers use interviewing techniques , observation , documentation and literature. By using key informants as a source of information and triangulation techniques as a source of data authenticity .After doing research, it was found that the performance of the Ombudsman of the Republic of Indonesia Representative Riau Province in the handling of public reports Pekanbaru city has been running well , but still not optimal due to the completion of reports requires a procedure that is quite complex and is still the lack of public knowledge of Pekanbaru on the existence of the Ombudsman as well as the functions and tasks.Keywords: Performance , maladministration , Responsiveness , Responsibility , Acountability.